Non-cefazolin antibiotic prophylaxis is associated with increased rates of acute infectious, medical, and surgical complications following primary total shoulder arthroplasty: a database study - Ryan D. Freshman, MD; Amir Fathi, BS; Matthew Orringer, MD; Jacob L. Kotlier, BA; Cory K. Mayfield, MD; Eric H. Lin, BA; Cailan L. Feingold, BS; Frank A. Petrigliano, MD; Joseph N. Liu, MD (JSES International)
Hypothesis: This study aimed to evaluate different prophylactic antibiotic regimens and risk for acute postoperative readmissions, infections, and medical complications. Methods: This retrospective cohort study used the Premier Healthcare Database to identify patients who underwent primary elective shoulder arthroplasty procedures over the age of 18. The database was queried to identify perioperative antibiotic regimens using specific codes for cefazolin, clindamycin, and vancomycin. Patients receiving cefazolin monotherapy for prophylactic antibiotic regimen were used as a control group and multivariate logistic regression was then used to calculate odd ratios for postoperative complications within 90 days of the procedure. Results: A total of 139,032 patients undergoing primary shoulder arthroplasty between 2016 and 2020 were included. Cefazolin monotherapy was the most prescribed antibiotic regimen (59.3%), followed by vancomycin and cefazolin combination therapy (23.3%), vancomycin monotherapy (8.6%), clindamycin monotherapy (5.6%), and vancomycin and clindamycin combination therapy (3.2%). Monotherapy with clindamycin or vancomycin was associated with increased risk of periprosthetic joint infection (P < .001). Vancomycin use as monotherapy or combination with another antibiotic increased the risk of postoperative acute kidney injury (P = .017-.001). Conclusion: Compared to vancomycin and clindamycin monotherapy, cefazolin monotherapy was associated with a lower risk of developing acute postoperative periprosthetic joint infection. The results of this study support the use of cefazolin monotherapy as the current standard for patients undergoing primary total shoulder arthroplasty.